Asparaginase-specific basophil recognition and activation predict Asparaginase hypersensitivity in mice - Rathod, Sanjay; Hoshitsuki, Keito; Zhu, Yin; Ramsey, Manda; Fernandez, Christian A. (Frontiers in Immunology, 2024)
Asparaginase (ASNase) is a crucial part of acute leukemia treatment, but immune responses to the agent can reduce its effectiveness and increase the risk of relapse. Currently, no reliable and validated biomarker predicts ASNase-induced hypersensitivity reactions during therapy. We aimed to identify predictive biomarkers and determine immune cells responsible for anaphylaxis using a murine model of ASNase hypersensitivity. Our preclinical study uses a murine model to investigate predictive biomarkers of ASNase anaphylaxis, including anti-ASNase antibody responses, immune complex levels, ASNase-specific binding to leukocytes or basophils, and basophil activation. Our results indicate that mice immunized to ASNase exhibited dynamic IgM, IgG, and IgE antibody responses. The severity of ASNase-induced anaphylaxis was found to be correlated with levels of IgG and IgE, but not IgM. Basophils from immunized mice were able to recognize and activate in response to ASNase ex vivo, and the extent of recognition and activation also correlated with the severity of anaphylaxis observed. Using a multivariable model that included all biomarkers significantly associated with anaphylaxis, independent predictors of ASNase-induced hypersensitivity reactions were found to be ASNase immune complex levels and ASNase-specific binding to leukocytes or basophils. Consistent with our multivariable analysis, we found that basophil depletion significantly protected mice from ASNase-induced hypersensitivity reactions, supporting that basophils are essential and can be used as a predictive marker of ASNase-induced anaphylaxis. Our study demonstrates the need for using tools that can detect both immune complex-and IgE-mediated hypersensitivity reactions to mitigate the risk of ASNase-induced hypersensitivity reactions during treatment.